STUDI EXPLORASI IMPLEMENTASI INFORMED CONSENT PADA TINDAKAN KEGAWATDARURATAN OBSTETRI OLEH BIDAN DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KOTA SEMARANG - Lestari Puji Astuti; Dita Wasthu Prasida; Dewi Mayangsari (Universitas Muhammadiyah Semarang, 2017)
Background: The causes of maternal death are divided into two, direct and indirect causes. The direct causes of maternal death include complications of pregnancy, delivery, and parturition, i.e bleeding (30-35%), eclampsia (28.76%), infection (20-25%), gestosis (15-17%). Bleeding and eclampsia is an emergency case that requires fast and responsive midwife action. Problems arise when actions taken have substantial risks, requiring the midwife to seek informed consent.Objective: To explore midwives' perception of informed consent on emergency action. Exploring midwives' perception of informed consent requirements on emergency acion. Exploring midwives' perception of informed consent implementation on emergency action. Exploring obstacles to the implementation of informed consent on emergency action. Exploring efforts to overcome obstacle to the implementation of informed consent on emergency action.Research Method: This research uses qualitative method. Data collection techniques were used by in-depth interviews. The number of informants are 3 midwives who work in District Health Center of Semarang Health Office area.Results: The results of in-depth interviews on the informants obtained information about midwives perception in terms of informed consent is the approval in performing emergency, informed consent requirements that is administratively can be implemented after handling emergency, the implementation of informed consent is explained to the patient when handling emergency and administration can adjust the patient's condition, the implementation of informed consent due to the condition of the patient during the emergency and no one to deliver.Suggestion: For the District Health Center (Puskesmas) to involve health cadres in motivating pregnant women to check their pregnancy that accompanied by husband or family (to anticipate emerging emergency).Keywords: informed consent, obstetric emergency